Fecal Sludge Management Tools : Data Collection Instruments - World Bank Group (World Bank, Washington, DC, 2016)
This document contains data collection instruments to support data collection, for which the resulting data will inform diagnostic and decision-making tools for Fecal Sludge Management (FSM) services. The diagnostic and decision-making tools shown are those developed in a World Bank global FSM study (2016) that are further described in (i) a Summary Report of the FSM study (ii) Tools and Guidelines for improving fecal sludge management (FSM) services.